The Role of Coastal Women in Increasing Household Income in Kamal District, Bangkalan Regency, Madura Island - Setiani, Setiani; Laelia, Wanti Nusrul (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
The participation of women living in coastal areas in economic endeavors is influenced by unmet household needs which is influenced mainly by the relatively low income generated by their husbands as fishermen. This study aims to understand the role of coastal women in increasing household income in Tajungan Village, Kamal District, Bangkalan Regency, Madura. It identifies their types of work, opinions on their roles, working time allocation, and their contribution to household income. Applying a descriptive-quantitative method, this study finds that coastal women engage in various jobs, including housewives, fish sellers, cracker processors, shopkeepers, domestic helpers, fishing laborers, and shrimp paste processors. More than 70% of coastal women are involved in sales and possess strong financial management skills. They balance household duties and support the local economy, fostering a happy and healthy environment in the home. They spent most of their time resting (38%), compared to productive activities (26%). Although they make a small contribution (25.3%), their income still plays an important role for their families. Skill development programs, financial access, and better support systems for domestic responsibilities are needed to enhance productivity, income, and balance dual roles, improving household welfare.